Peer leadership and shared mental models in a college volleyball team: A season long case study - Filho, E. M.; Gershgoren, L.; Basevitch, I.; Schinke, R. J.; Tenenbaum, G. (Journal of Clinical Sport Psychology, 2014)
The present study was an initial attempt to capture and describe instances of shared mental models within a team from the point of view of the team captain. Specifically, the purpose of this study was to describe a range of perceived and shared behaviors aimed at facilitating the overall performance of a college volleyball team from the perspective of the team captain. This behavioral focus is congruent with the need for documenting observable task and team-related coordination mechanisms. Symbolic interactionism, via the use of systematic observations, documental analysis, and semistructured open-ended interviews, was used to gather data from the participant in the form of a case study. Data were analyzed using Braun and Clarke's (2006) theoretical thematic analysis based on categories derived from Eccles and Tenenbaum's (2004) Conceptual Framework of Coordination in Sport Teams. Results indicated that the player's actions were perceived as enhancing proactive information sharing within her team. Therefore, it is suggested that team leaders possess important objective and symbolic roles in the promotion of shared mental models. These results are further discussed in relation to current knowledge of shared mental models in sports. Limitations and directions for future research are outlined.